Curcuma zedoaria (Christm.) Roscoe (MANFAAT DAN BIOAKTIVITAS) - Dr. Marina Silalahi, M.Si (Jurnal Pro-Life, 2018)
Curcuma zedoaria (Christm.) Roscoe or temu putih is native plant in India, have been long cultivated in Indonesia. By the local commuities in Java, its have been used as component of the jamu and the traditional maedicine. This article is based on literature offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Based on a study of ethnobotany Curcuma zedoaria used as medicine and spices. The main of secondary metabolites of Curcuma zedoaria rhizomes are terpenoids esspecially seskuiterpenoid and monoterpenoid. Curcuma zedoaria have bioactivities as anticholesterol, anti tumor/ canker, anti inflamation, demam, antipiretik, analgesic dan anti microbial.Keywords: Curcuma zedoaria, essential oil, antioksidan, dan antimikroba.